The progression of shoulder functional profile in male rugby union players from the academy to the professional level - Rogowski, I.; Degot, M.; Capel, O.; Vigne, G.; Loursac, R.; Hager, J.-P.; Blache, Y.; Neyton, L. (Physical Therapy in Sport, 2025)
Objective To investigate the changes in shoulder functions with age, playing position, dominance and injury history in elite male rugby union players.